So Close Yet So Far: Perspectives on the South African Police Service’s Response to Murder Cases in the Wallacedene Policing Area - Tsoho, Nthabiseng Patricia; Mofokeng, Jacob Tseko; Dorcas, Khosa (Technium Social Sciences Journal, 2021)
The aim of this study was to determine views of the South African Police Service’s (SAPS) response to murder cases in the Wallacedene policing area; the contributing factors that lead to the failure of the police to prosecute offenders; the effectiveness of strategies to reduce murder-related incidents in the study area; the contributing factors to murder in the Wallacedene policing area; and to make recommendations to improve the conviction rate. Twenty-five participants were selected for this study. A qualitative approach was used, with semi-structured interviews as the data-collection tool. The findings highlighted that there is a lack of partnership between SAPS detectives and the community. The contributing factors for the police to fail prosecuting offenders. Reasons for the current problem include inexperienced detectives and lack of resources. In order to increase the performance of the detectives and the first responders to the scene, the research explored the challenges encountered by the SAPS detectives and makes suggestions and recommendations to increase their efficiency.